THE RELATIONSHIP BETWEEN LIFE STYLE WITH THE INCIDENCE OF PRIMARY DYSMENORRHEA IN MEDICAL FACULTY FEMALE STUDENTS OF TANJUNGPURA UNIVERSITY - Ghina Tsamara; Widi Raharjo; Eka Ardiani Putri (Jurnal Nasional Ilmu Kesehatan, 2020)
Background: Primary dysmenorrhea is a menstrual pain with no pelvic pathology that often occurs at age 15-25 and can be caused by several factors. Life stye like the level of stress, physical activity and fast food consumption can be the factors of the incidence of primary dysmenorrhea. Purpose: To determine the relationship between life style (level of stress, physical activity, and fast food consumption) with primary dysmenorrhea in Medical Faculty Female Students of Tanjungpura University. Methodology: Observational analytical research with approach design research type cross-sectional. A total of 48 people were involved in this experiment. Variable on this research were primary dysmenorrhea, level of stress, level of physical ativity, and fast food consumption. Data collection through Numering Rating Scale, Kessler Psychological Distress Scale Questionnaire, Global Physical Activity Questionnaire, and Food Frequency Questionnaire. Result: Respondents who had primary dysmenorrhea were 70,8%. Respondents with level of mild stress were 31,3%. Respondents with level of mild physical activity were 66,7%. Respondents who usually consumed fast food were 60,4%. The statistical test result between primary dysmenorrhea with level of stress (p=0,025), level of physical activity (p=0,000), and fast food consumption (p=0,000). Conclusion: There are relationship between primary dysmenorrhea with level of stress, level of physical activity and fast food consumption among Medical Faculty Female Students of Tanjungpura University.Keywords: primary dysmenorrhea, lifestyle, stress, physical activity, fast food.